Analisis Pengaruh Keselamatan Dan Kesehatan Kerja Terhadap Kinerja Pelaksanaan Proyek Instalasi Pengelolaan Air SPAM Maminasata - La Ode Muhammad Syawal; Savitri Prasandi Mulyani; Suryani Syahrir (Jurnal Penelitian Teknik Sipil Konsolidasi, 2026)
The construction project development process is generally an activity that contains many elements of danger. This causes the construction industry to have a poor record in terms of occupational safety and health. This study aims to analyze the effect of the implementation of Occupational Safety and Health on project performance and to determine the dominant factors that influence the performance of workers in the 500l/sec capacity IPA construction project for the Maminasata SPAM, South Sulawesi Province, phase 1. This type of research is a quantitative research type with numerical analysis using the SPSS application. The results of this study obtained two variables that influence the performance of project workers, namely the work safety variable (X1) and worker health (X2) and the dominant factor that influences performance is worker health (X2).